Tarkovsky cinema as poetry - Turovskaya, Maya; Ward, Natasha; Christie, Ian (London Faber and Faber Limited, 1989)
This is the first book about Andrey Tarkovsky by a leading Soviet critic to be translated into English. Maya Turovskaya was one of the first to hail Tarkovsky's originality when she saw Ivan's Childhood in 1962. Having followed his career ever since, she has a close familiarity with his sources--especially the poetry of his father Arseniy Tarkovsky--as well as with the archives of Mosfilm Studios.

In his introduction, Ian Christie places the work of Tarkovsky in the context of Soviet cinema, showing how Tarkovsky broke with the tradition of Soviet art in cinema and created his unique, visionary cinematic identity.

This critical study is a companion volume to Tarkovsky's own work, Sculpting in Time, which is also published by Faber and Faber.
"First published in a West German edition as Andrei Tarkovsky: Film als Poesie, Poesie als Film in 1981"--P. xxiv.
Translated from Russian.
Filmography (pages 165-169).
Includes bibliographical references (pages 170-171) and index (pages 173-177).
Keywords: Tarkovskiĭ, Andreĭ Arsenʹevich -- 1932-1986 -- Criticism and interpretation